Condicionadores de Ar Inverter: Modelagem Computacional e Curvas de Suportabilidade para Estudos de Pedidos de Ressarcimento por Danos Elétricos - Oliveira, Humberto Cunha (2020)
The considerable increase in claims by electrical damages has caused several misfortunes to energy utilities and their consumers. These claims comprise not only financial losses, but also social impacts resulting from legal conflicts between both parties. Such concerns triggered the emergence of the area called Damage Compensation Claims, mainly aimed at improving and at systematizing the process of verifying reimbursement cases, provided by the Brazilian Electricity Regulatory Agency. After including in the causal nexus consistency analysis methodology new mathematical and computational fundamentals and laboratory tests, utilities can perform fair and cohesive cases assessment. Based on works found in the literature, there is scientific basis that justifies the inclusion of studies for new electronic equipment in a computational environment. Thus, with a focus on the new inverter technology integrated with split air conditioners, this master thesis is addressed to develop a comprehensive reimbursement study that provides the necessary information for evaluating the cases with these devices. In this context, the objective is to propose an electrical computational model of the air conditioner, responsible for providing the dielectric and thermal stresses imposed on the device, with its dielectric and thermal withstand limits. From this information, it will be possible to compare and verify the veracity of cause and effect between the equipment and disturbances manifested in the networks. Therefore, it is expected from this work that more consistent analyses of possible reimbursement cases are conducted with new parameters and methods.